Exercise training reduces high mobility group box-1 protein levels in women with breast cancer: findings from the DIANA-5 study - Francesco Giallauria; Marco Gentile; Paolo Chiodini; Franco Berrino; Amalia Mattiello; Luigi Maresca; Alessandra Vitelli; Maria Mancini; Alessandra Grieco; Angelo Russo; Rosa Lucci; Giorgio Torella; et al. (Monaldi Archives for Chest Disease, 2015)
Purpose: To determine whether exercise training might exert anti-inflammatory effect by reducing HMGB1 levels in women with breast cancer (BC). Methods: We analyzed monocentric data from the DIANA (DIET AND ANDROGENS)-5 PROJECT. Study population consisted of 94 patients randomized into two groups: 61 patients (53±8 yrs, training group) were assigned to a structured exercise training intervention (3 times/week for the first 3 months, and once /week for the following 9 months); whereas 33 patients (52±7 yrs, control group) followed only the general indications to adhere to the life-style intervention suggestions of the DIANA protocol. At study entry and after 12 months, all patients underwent cardiopulmonary exercise testing, biochemical assessment [HMGB1, high-sensitivity C-reactive protein (hs- CRP), interleukin-6 (IL-6)]; and lipid and glycemic profile. Results: There were no significant differences between groups in baseline clinical and inflammatory profile. Among the training group, only 19/61 patients had high adherence to the exercise intervention. After stratifying the study population according to the level of adhesion to the exercise intervention, 1-year HMGB1 levels were lower among patients more adherent to exercise (p for trend=0.001). Further adjusting for age, body mass index and baseline values, 1-year HMGB1 levels remained significantly and inversely associated to the level of adhesion to the exercise intervention (B=-0.97, SE=0.43, p=0.01). Conclusions: Moderate intensity exercise training in BC survivors is associated with reduced HMGB1 levels that are proportional to the level of adhesion to the exercise intervention, independently from other classical inflammatory molecules, suggesting an exercise-induced anti-inflammatory effect mediated by HMGB1.